2018
DOI: 10.1111/birt.12350
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for nonreassuring fetal heart rate tracings after artificial rupture of membranes in spontaneous labor

Abstract: Nonreassuring FHR after AROM during delivery is associated with parity, fetal station at AROM, birthweight, and oxytocin augmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
7
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 21 publications
6
7
1
Order By: Relevance
“…On the other hand, this finding contrasts with the case control study conducted in Israel [ 21 ] where being primigravida decreased the risk of developing NRFHRP. This might be due to proper ANC counselling as many of the participants in the Israel study had ANC follow-up.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…On the other hand, this finding contrasts with the case control study conducted in Israel [ 21 ] where being primigravida decreased the risk of developing NRFHRP. This might be due to proper ANC counselling as many of the participants in the Israel study had ANC follow-up.…”
Section: Discussioncontrasting
confidence: 91%
“…Mothers who had augmentation of labor were 3 times more likely to develop NRFHRP than mothers who had no augmentation. In a similar manner, a study conducted in Israel showed that oxytocin augmentation significantly increased the risk for NRFHRP [ 21 ]. The administration of oxytocin to correct uncoordinated labor patterns confers a risk for increase in uterine contraction frequency and decrement of uterine blood flow which causes hypoxemia and disturbs the FHR pattern [ 22 ].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Many medical and obstetrics factors like antepartum haemorrhage (APH), amniotic fluid disorders, induction/augmentation of labor, intrauterine growth restriction (IUGR), use of anesthesia, presence of MSAF, abnormal fetal presentation and intraoperative findings like (uterine rupture, cord entanglements or placental abruption were the risk factors identified to have association with NRFHS (10, 20, 21).…”
Section: Introductionmentioning
confidence: 99%
“…NRFHRS tracing was described as requiring necessitates immediate intervention like caesarean section or instrumental vaginal delivery (11, 21), intrauterine resuscitation, including oxytocin deprivation and amnioinfusion (20) to prevent or reduce bad neonatal outcome. But determining the most effective strategy in the case of abnormal FHR tracings is so difficult.…”
Section: Introductionmentioning
confidence: 99%